Release from life - release in life: Indian perspectives on individual liberation ; [papers presented at the Symposium "Erlöst Leben - Oder Sterben, Um Befreit zu Werden?" (Zurich, May 2008), organized in honour of Peter Schreiner] - Bigger, Andreas; Schreiner, Peter (Worlds of South and Inner Asia, 2010)
"Festschrift in honour of Peter Schreiner